Teaching academic English in higher education: strategies and challenges - Li, Honghuan (Frontiers in Education, 2025)
This narrative review explores the strategies and challenges associated with teaching Academic English (EAP) in higher education, summarizing recent research findings and practical evidence. With the expansion of global academia, proficiency in academic English has become vital for students and institutions. The review examines learner-centered, multimodal, and technology-driven instructional strategies, such as virtual reality (VR) and artificial intelligence (AI), that support effective language acquisition. It also discusses persistent challenges, including varying student proficiency, insufficient teacher training, and difficulties in technology implementation, highlighting their impact on teaching outcomes. The issue of biases toward non-native English teachers is also examined. Empirical studies reveal successful approaches such as blended learning and structured teacher development programs. Recommendations emphasize institutional commitment, targeted professional development, and strategic technology use. Suggestions for future research include deeper investigation into critical thinking, digital literacy, intercultural competence, and sustainable EAP program effectiveness.